The relationship between self-assessment of language proficiency and measures of lexical diversity and syntactic complexity: evidence from bilingual speakers of Italian in Croatia - Hržica, Gordana; Košutar, Sara; Poropat Jeletić, Nada (Frontiers in Communication, 2024)
A wide range of tools have been used to assess the language proficiency of bilingual speakers. The validity and high reliability of lexical diversity and syntactic complexity measures as instruments for measuring language proficiency have been demonstrated in previous studies across different languages. However, the relationship between self-assessment and the two measures has not yet been investigated. The present study focused on the Italophone bilingual language speakers, an understudied minority diglossic community in Croatia, and investigated whether measures of lexical diversity and syntactic complexity reflect self-assessment of language proficiency in the standard Italian language and the Istrovenetian dialect overall and in four specific domains (reading, writing, speaking, and listening). In addition, we aimed to investigate whether there are possible differences in self-assessment between the standard Italian language and the Istrovenetian dialect and whether there are language variety-related differences (standard vs. dialect) in the relationship between self-assessment and measures of lexical diversity and syntactic complexity. The results showed an intricate interplay between self-assessment and the lexical diversity and syntactic complexity of bilingual speech. This suggests that these measures are interrelated and that heritage bilingual language speakers may be able to objectively assess their language proficiency.